Effectiveness of Active Cycle of Breathing Technique on Respiration Rate in Chronic Obstructive Pulmonary Disease Patients: A Scoping Review - Fariz Yulian Pratama; Meira Erawati; Rita Hadi Widyastuti (Indonesian Journal of Global Health Research, 2025)
A prolonged cough, excessive sputum production, narrowing of the airways, and shortness of breath or a decrease in respiration rate were symptoms caused by COPD. One of the breathing exercise methods that could help expel sputum, maintain lung elasticity, reduce shortness of breath, and improve lung function was the Active Cycle of Breathing Technique (ACBT). ACBT was often given to patients with lung problems; therefore, a review was necessary to determine the effectiveness of ACBT on the respiration rate of COPD patients. Objective: This study aimed to determine the effectiveness of the Active Cycle of Breathing Technique on the respiration rate of patients with COPD. Method: Literature sources were searched using online databases such as ScienceDirect, ProQuest, CambridgeCore, Oxford Academic, SpringerLink, and Google Scholar. The keywords used for the search included Active Cycle of Breathing Technique, Respiration Rate, and COPD Patients. The articles obtained were then analyzed to identify differences and similarities among the articles. The articles were identified using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The extracted data were compiled into a table. Results: From a total of 3,835 articles, 5 articles met the inclusion criteria. Conclusion: The review results indicated that the Active Cycle of Breathing Technique (ACBT) was effective in reducing the respiratory rate (RR) in patients with COPD.